Perilaku School Bullying Pada Siswa Sekolah Dasar - Putu Yulia Angga Dewi (Edukasi: Jurnal Pendidikan Dasar, 2020)
Behavior in children can be classified as normal or abnormal behavior. Children's behavior can be said to be normal if the behavior is in accordance with that in society. While children's behavior can be said to be abnormal if the child's behavior has deviated from the prevailing order in the community so that the community directly or indirectly rejects it. Children who are accustomed to observing and even experiencing violence both physically and verbally in the home environment or play, later children will build a framework that is a natural thing and needs to be done. Hurlock (1978: 221) says anger is an expression that is more often expressed in children. The reason is because the stimulation that causes more anger in children, children also know that anger is an effective way to get attention or fulfill their desires. Keywords: School Bullying, Elementary school student